Test flattening in the larger foraminifer Heterostegina depressa: predicting bathymetry from axial sections. Issue 1 (24th January 2018) - Eder, Wolfgang; Hohenegger, Johann; Briguglio, Antonino
Abstract: Previous attempts to quantify the test-flattening trend in Heterostegina depressa with water depth have been rather unsuccessful. Due to its broad depth distribution, H. depressa is a perfect model species to calibrate test flattening as a bathymetric signal for fossil assemblages. This might enable us to better reconstruct paleoenvironments of fossil communities of larger foraminifera or even provide clues to the degree of transport in allochthonous deposits. In this study, we used growth-independent functions to describe the change of test thickness throughout ontogeny. Four growth-invariant characters, deriving from these functions, clearly quantify a transition of individuals with thicker to thinner central parts along the water-depth gradient. This transition is probably controlled by light intensity, because the photosymbionts of H. depressa (diatoms) are most effective at low irradiation levels. Thus, specimens at shallower depths grow thicker to reduce light penetration, whereas specimens living deeper than the light optimum increase their surface by flattening to obtain better exposure to light.